Two loci on chromosome 9 control bile acid composition: evidence that a strong candidate gene, Cyp8b1, is not the culprits⃞ - Ephraim Sehayek (Journal of Lipid Research, 2006)
An intercross between C57BL/6J and CASA/Rk mice was used to study the genetics of biliary bile acid composition. In parental strains, male C57BL/6J mice had significantly higher cholic acid (CA; 14%) and lower β-muricholic acid (βMC; 27%) than CASA/Rk mice, whereas females did not differ. However, quantitative trait locus analysis of F2 mice revealed no significant chromosome 9 loci in males but loci in females on chromosome 9 for percentage CA (%CA) at 72 centimorgan (cM) [logarithm of the odds (LOD) 5.89] and %βMC at 54 cM (LOD 4.09). Chromosome 9 congenic and subcongenic strains representing CASA/Rk intervals 38–73 cM (9KK) and 68–73 cM (9DKK) on the C57BL/6J background were made. In 9KK and 9DKK males, %CA was increased and %βMC was unchanged, whereas in 9KK but not 9DKK females, %CA was increased and %βMC was decreased. Sterol 12α-hydroxylase (Cyp8b1) channels bile acid precursors into CA and maps at chromosome 9 (73 cM). However, there was no significant difference in Cyp8b1 mRNA or enzymatic activity between parental mice, parental-congenic-subcongenic mice, or high-low biliary %CA F2 mice. In summary, two chromosome 9 loci control sexually dimorphic effects on biliary bile acid composition: a distal (68–73 cM) major determinant in males, and a more proximal (38–68 cM) major determinant in females. In this intercross, Cyp8b1, a strong candidate, does not appear to be responsible.